Edukasi Pencegahan Demam Berdarah Dengue Berbasis Kebersihan Lingkungan Pada Masyarakat Desa Candimas, Natar, Kabupaten Lampung Selatan - Emantis Rosa; Hendri Busman; Yulianti (CV. Multi Kreasi Media, 2026)
Aedes aegypti mosquito is the main vector for Dengue Fever (DHF), a type of disease that remains a significant public health issue in Indonesia. Even though various control efforts have been carried out, cases of this disease continue to be reported every year in changing numbers. One effective control strategy involves fostering community-wide engagement to eliminate mosquito breeding sites through improving environmental cleanliness—an important factor influencing the existence of breeding sites, both inside and outside the home. To achieve these activity objectives, an educational program and information dissemination has been implemented for the community in Candimas Village Natar Region, South Lampung Regency. The results show an increase in knowledge and understanding among the target group namely the residents of Candimas Village as evidenced by an increase in scores from 73.9% in the initial assessment to 87.85% in the final assessment, which represents an average increase of 42.14%.